FINANCIAL REPORTING MANIPULATION ON MINING COMPANIES IN INDONESIA: FRAUD DIAMOND THEORY APPROACH - Yonathan Daya Persada; Roni Budianto; Eko Suyono; Sofiatul Khotimah; Atiek Sri Purwati (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
Forensic accounting helps to discover fraud practices where the fraud diamond theory is one of the popular theories in this issue. It puts concerns on budget priorities, financial stability, inefficient monitoring, replacement of auditor and directors. As the dependent variable, financial statement manipulation funded by income control is used. The nine mining entities listed on the Indonesian Stock Exchange in 2017-2019 were chosen using the purposive sampling method, resulting in 27 observations. By using the multi-linear regression method, This study showed that financial targets and financial stability affect the occurrence of fraud in financial reports. Oppositely, insufficient monitoring, replacement of auditors and directors have no impact on the fraudulent reporting.